Review Article: Penggunaan Nanopartikel Kitosan sebagai Penghantar Obat Baru - Iin Lidia Putama Mursal; Ainun Maratus Putri Warsito; Dyah Kharisma Ariyanti; Elista Indah Susanti; Refriyanti Irma (Journal of Pharmaceutical and Sciences, 2023)
Nanoparticle technology is beneficial as a drug carrier is high stability, and high carrier capacity. This carrier system can be designed to allow continuous drug release from the matrix, a polymer used for the formation of nanoparticles, one of which is chitosan. Chitosan is a polymeric substance that is used to form nanoparticles. The research method used is to review articles from several Google Scholar databases, ScienceDirect, pubmed. The advantage of chitosan is that processing it into nanoparticles allows chitosan to be used as a more effective delivery agent for pharmaceutical compounds or drugs.